2021
DOI: 10.3389/fimmu.2021.676082
|View full text |Cite
|
Sign up to set email alerts
|

IFN-I Mediates Lupus Nephritis From the Beginning to Renal Fibrosis

Abstract: Lupus nephritis (LN) is a common complication of systemic lupus erythematosus (SLE) and a major risk factor for morbidity and mortality. The abundant cell-free nucleic (DNA/RNA) in SLE patients, especially dsDNA, is a key substance in the pathogenesis of SLE and LN. The deposition of DNA/RNA-immune complexes (DNA/RNA-ICs) in the glomerulus causes a series of inflammatory reactions that lead to resident renal cell disturbance and eventually renal fibrosis. Cell-free DNA/RNA is the most effective inducer of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 230 publications
(272 reference statements)
0
37
0
Order By: Relevance
“…Thus, regional viral and “pseudo” viral immunoreactions, including proinflammatory cytokines/chemokines production via the activation of TLR3 signaling in the intrinsic glomerular cells have been postulated to be involved in the pathogenesis of LN [ 3 , 6 , 7 , 24 ]. Furthermore, sustained activation of type I IFN is believed to participate in LN pathogenesis [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, regional viral and “pseudo” viral immunoreactions, including proinflammatory cytokines/chemokines production via the activation of TLR3 signaling in the intrinsic glomerular cells have been postulated to be involved in the pathogenesis of LN [ 3 , 6 , 7 , 24 ]. Furthermore, sustained activation of type I IFN is believed to participate in LN pathogenesis [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained activation of type I interferon (IFN) has been reported to play a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE) and the development of lupus nephritis (LN) [ 1 , 2 ]. Therefore, the involvement of innate immune system upregulation via regional Toll-like receptor (TLR) signaling, such as TLR3, TLR7, and TLR9, is believed to be involved in LN pathogenesis [ 3–7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type I IFN has previously been found to mediate LN from the initial stages to the development of renal fibrosis [ 27 , 34 ]. At the initial stages, type I IFN contributes to formation of IC as well as decreased clearance of ICs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the initial stages, type I IFN contributes to formation of IC as well as decreased clearance of ICs [ 35 ]. It has been shown that renal resident cells rather than infiltrating immune cells are a main source of type I IFN [ 34 ] and can be stimulated through TLR by way of nucleic acid products including DNA and RNA-immune complexes which can induce IFNβ in renal medullary cells (RMC) [ 9 , 36 ]. Thus, IFNβ can have a dual factor of inducing IC, as well as decreasing clearance of ICs at the acute stage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, dd-cfDNA may itself represent a danger signal that initiates an immune response in the form of dendritic cell (DC) activation. In a parallel vein, high levels of mitochondrial DNA (mtDNA) are found in the circulation of patients suffering from sepsis, trauma, and chronic organ-specific illnesses such as rheumatoid arthritis, gout, SLE, and hepatitis [ 56 , 57 , 58 , 59 ]. In transplantation, mtDNA is also released following allograft reperfusion and has also been shown to be a compelling danger signal that is recognized by the innate immune system, directly modifying the inflammatory response.…”
Section: The Nlrp3 Inflammasome and Dna Sensingmentioning
confidence: 99%